Wages and Labor Markets before the Civil War - Margo, Robert A. (American Economic Review, 1998)
Documenting and explaining economic events in the past is the central task of economic history. This activity needs no more justification than any other type of pure economic research. But economic history can also provide useful perspective when events in the past share commonalities with events in the present, thereby rendering current economic change less mysterious or forbidding. This paper describes a long-term research project aimed at documenting certain aspects of the economic history of labor in the United States before the Civil War. Although the labor history of the antebellum period seems remote from modern concerns, there are, perhaps surprisingly, numerous parallels-for example, changes in wage inequality, realwage stagnation, high rates of unskilled inimigration, the effects of labor-market conditions on welfare usage, wage rigidity and macroeconomic fluctuations, and convergence of geographically distinct labor markets.